Research on Photo Catalytic Performance of TiO2 Film Doped with Li+ - Zhang Jing; Huang Zhengxing; Zheng Liming; Tian Xiaobo; Yin Wengang; Ding Shihua (MATEC Web of Conferences, 2022)
Based on sol-gel method and spin coating process, TiO2 film doped with Li+ is prepared by utilizing analytical pure butyl titanate, lithium nitrate, absolute ethanol, glacial acetic acid, acetylacetone and deionized water as raw material. The Li+ ion which has equal radius as Ti4+ ion is chosen in experiments for doping and modification. Experimental results show certain increase of catalytic efficiency in TiO film doped with Li+. However, the increase level of catalytic efficiency gradually shows some decrease when the dopant amount changes from 0.025mol to 0.1mol. Catalytic efficiency is raised to 25.7% when the dopant amount is 0.025mol.